Divided-pulse nonlinear compression in a multipass cell - Stark, Henning; Grebing, Christian; Buldt, Joachim; Klenke, Arno; Limpert, Jens (JPhys Photonics, 2022)
The pulse-energy and peak-power limitations of a gas-filled multipass cell (MPC) for nonlinear pulse compression are surpassed by applying a burst of four temporally separated pulses instead of a single one. The burst is generated by two birefringent crystals and contains 1mJ of energy per pulse replica. It is then spectrally broadened in an Argon-filled MPC and recombined into a single pulse by a second set of birefringent crystals. The combined pulse is compressed by chirped mirrors to a pulse duration of 32fs and a pulse energy of 3.4mJ . An excellent passive stability and a high system efficiency of > 90% are reached. Using the 4-pulse burst, the overall output energy supported by the MPC is doubled in comparison to single-pulse operation.
CRIS-Team Scopus Importer:2023-04-20
Keywords: coherent combining; divided-pulse nonlinear compression; multipass cells; ultrafast fiber lasers